A modelling study on hydrolysis of whey lactose and stability of β-galactosidase - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2010)
In the present study, the effect of process conditions on whey lactose hydrolysis and enzyme inactivation were investigated. The experiments were carried out in 250 mL of 25 mM phosphate buffer solution by using beta-galactosidase produced from Kluyveromyces marxianus lactis in a batch reactor system. The degree of lactose hydrolysis (%) and residual enzyme activity (%) against time were investigated versus lactose concentration, enzyme concentration, temperature and pH. The mathematical models were derived from the experimental data to show the effect of process conditions on lactose hydrolysis and residual enzyme activity (in the presence and absence of lactose). At the optimum process conditions obtained (50 g/L of lactose concentration, 1 mL/L of enzyme concentration, 37 degrees C of temperature and pH 6.5), 81% of lactose was hydrolyzed and enzyme lost its activity by 32%. The activation energy for hydrolysis reaction (E-A) and the enzymatic inactivation energy (E-D) were calculated as 52.7 kJ/mol and 96.7 kJ/mol. Mathematical models at various process conditions have been confirmed with the experimental results.
Keywords: Whey Lactose Hydrolysis; beta-Galactosidase; Process Conditions; Kinetic Study; Modelling; ENZYME DEACTIVATION; PRODUCT INHIBITION; ESCHERICHIA-COLI; BED REACTOR; IMMOBILIZATION; SUPPORTS; BATCH; MILK; Chemistry; Engineering